2022
DOI: 10.1177/03635465221092762
|View full text |Cite
|
Sign up to set email alerts
|

Basketball Players Undergoing Primary Hip Arthroscopy Exhibit Higher Grades of Acetabular Cartilage Damage but Achieve Favorable Midterm Outcomes and Return to Sports Rates Comparable With a Propensity-Matched Group of Other Cutting Sports Athletes

Abstract: Background: Favorable short-term outcomes in competitive basketball players have been reported. Midterm outcomes in these athletes and how they compare with athletes in sports with similar demands have not been well established. Purpose: (1) To report minimum 5-year patient-reported outcomes (PROs) and return to sports data in competitive basketball players undergoing primary hip arthroscopy for femoroacetabular impingement syndrome (FAIS) and (2) to compare outcomes with a propensity-matched control group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 70 publications
(104 reference statements)
2
5
0
Order By: Relevance
“…22 Interestingly, the present study reports high rates of cartilage damage, with over 30% of the athletes exhibiting ALAD grade 3 or 4 damage. This is consistent with a recent study by Owens et al, 40 who reported that basketball athletes at midterm outcomes exhibited >30% ALAD grade 3 or 4 damage and had a 3.6% conversion rate to THA. Cartilage damage may be an indicator for negative outcomes; however, when compared with the general population, athletes have higher outcomes 45 and may have lower rates of conversion to THA, given their higher pain tolerance than the general population.…”
Section: Discussionsupporting
confidence: 93%
“…22 Interestingly, the present study reports high rates of cartilage damage, with over 30% of the athletes exhibiting ALAD grade 3 or 4 damage. This is consistent with a recent study by Owens et al, 40 who reported that basketball athletes at midterm outcomes exhibited >30% ALAD grade 3 or 4 damage and had a 3.6% conversion rate to THA. Cartilage damage may be an indicator for negative outcomes; however, when compared with the general population, athletes have higher outcomes 45 and may have lower rates of conversion to THA, given their higher pain tolerance than the general population.…”
Section: Discussionsupporting
confidence: 93%
“…While athletes often subject their hips to unique and strenuous demands, resulting in higher rates of acetabular cartilage injury, the current study demonstrates high survivorship rates at the midterm follow-up, which was similar to that observed in Control patients. 41 This study found comparable rates of revision HA between CA (5.3%) and Controls (3.9%), with no patients converting to THA in either group. These findings align with those reported in the literature, where secondary revision surgery rates ranged from 3.6% to 15.2% in athletes, and conversion to THA rates ranged from 0% to 33%.…”
Section: Discussionsupporting
confidence: 50%
“…An a priori power analysis was calculated to determine the number of hips required in each group to detect 80% power with a 1:1 matching ratio. Based on an expected mean difference in the mHHS of 8 points and a standard deviation of 10, 15,31 the power analysis determined that 26 hips undergoing gluteus medius repair with the tendon compression bridge technique and 26 hips undergoing gluteus medius repair with the transtendinous technique would be required.…”
Section: Methodsmentioning
confidence: 99%